Durability of bond strength to dentin using two universal adhesives in different etching modes - Salem, Amany A. (2021)
Aim. To evaluate the bond durability of two universal adhesives; mild and ultra-mild in both etch-and-rinse and self-etch modes after simulated in-vitro degradation by long-term water storage or thermocycling. Methods. A total of 144 specimens were used in this study; 120 specimens (prepared from 30 teeth) for microshear bond strength testing and fracture mode assessment, and 24 specimens for scanning electron microscopic evaluation (prepared from 24 teeth). Specimens were prepared from 54 recently extracted caries free third molars and randomly divided into 12 groups, according to the adhesive treatment (All Bond or Scotchbond Universal), etching mode (etch-andrinse or self-etch) and aging method (thermocycling or water storage). Each tooth was sectioned mesio-distally into two halves exposing free dentin surface for bonding where dentin substrate 1 mm below the dentino-enamel junction was used. After adhesive application and composite build up, specimens were tested in shear mode after storing in distilled water at 37˚C for 24 hours or 1 year, or after being thermocycled between 5 and 55 °C for 10,000 cycles (n=10). Microshear bond strength (μSBS) was tested using a universal testing machine. Adhesive-dentin interface was examined using scanning electron microscope (SEM) (n=2). Data were analyzed using 3 way AN0VA and pairwise comparisons was performed using Bonferroni correction at significance level of α ≤0.05. Results. Statistical analysis revealed non-significant difference for etching mode in both adhesives (p=0.596). After aging, the bond strength was only reduced in Scotchbond Universal after one year of water storage in both modes (p<0.001). SEM evaluation revealed intact hybrid layer and longer resin tags for etch-and-rinse mode than selfetch mode of both adhesives. Conclusion. The bond strength of universal adhesives is not affected by the etching mode, however its durability was shown to be material dependent.